2009
DOI: 10.1159/000192587
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cannabinoids upon the Uptake of Folic Acid by BeWo Cells

Abstract: Folic acid (FA) is an essential micronutrient that is particularly important during pregnancy for normal placental and fetal development and growth. The placenta and the fetus become frequently exposed to drugs of abuse such as cannabinoids because of maternal use of these substances. The aim of this study was to investigate the influence of cannabinoids on the uptake of FA by BeWo cells. Acute treatment with anandamide (1–10 μmol/l) caused a 15% decrease in 3H-FA uptake at pH 7.5. Moreover, tetrahy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 53 publications
0
21
0
Order By: Relevance
“…These authors suggested that low folate level occurs most likely due to nutritional constraint. There are also studies showing that cannabinoids may impair the uptake of folate into BeWo cells (Araujo et al 2009) and human syncytiotrophoblasts (Keating et al 2009). However, the exact mechanism of this interaction remains unclear and requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…These authors suggested that low folate level occurs most likely due to nutritional constraint. There are also studies showing that cannabinoids may impair the uptake of folate into BeWo cells (Araujo et al 2009) and human syncytiotrophoblasts (Keating et al 2009). However, the exact mechanism of this interaction remains unclear and requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…BeWo cells form a well-differentiated monolayer, undergo syncytialization, and secrete hCG (8,35,58). They have been used widely in placental transport studies, e.g., glucose (1,3,6,13,25,38), amino acid (25,26,42), iron (12,18), fatty acid (24,60), and drug and toxic studies (2,22,36,47). BeWo cells express NIS and pendrin and demonstrate significant uptake and efflux of iodide, with kinetic and inhibitory characteristics consistent with these transporters (37).…”
Section: Discussionmentioning
confidence: 99%
“…They have been used widely in placental transport studies, e.g. glucose (Antony, et al 2007;Araujo, et al 2008;Baumann, et al 2007;Di Simone, et al 2009;Mark and Waddell 2006), amino acid (Jones, et al 2006a, b;Novak, et al 2006), iron (Danzeisen andMcArdle 1998;Gambling, et al 2001), fatty acid (Johnsen, et al 2009;Tobin, et al 2009), and drug and toxicity studies (Araujo, et al 2009;Hirano, et al 2008;Magnarin, et al 2008;Prouillac, et al 2009). BeWo cells express both of the iodide transporters, NIS and Pendrin (Manley et al 2005).…”
Section: Cell Model For Study Of Placental Iodide Transportmentioning
confidence: 99%